2016
DOI: 10.1016/j.bpj.2016.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Positive Quantitative Relationship between EMT and Contact-Initiated Sliding on Fiber-like Tracks

Abstract: Epithelial-mesenchymal transition (EMT) is a complex process by which cells acquire invasive properties that enable escape from the primary tumor. Complete EMT, however, is not required for metastasis: circulating tumor cells exhibit hybrid epithelial-mesenchymal states, and genetic perturbations promoting partial EMT induce metastasis in vivo. An open question is whether and to what extent intermediate stages of EMT promote invasiveness. Here, we investigate this question, building on recent observation of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…During the 12 days, cells were passaged at the regular frequency using the aforementioned standard methods, with the exception that cells were maintained in 20 ng/ml TGFβ-containing growth medium. This protocol matches exactly that used in our earlier work to quantify morphological and protein-expression changes induced by TGFβ treatment (11).…”
Section: Cell Culture and Tgfβ Treatmentmentioning
confidence: 56%
See 2 more Smart Citations
“…During the 12 days, cells were passaged at the regular frequency using the aforementioned standard methods, with the exception that cells were maintained in 20 ng/ml TGFβ-containing growth medium. This protocol matches exactly that used in our earlier work to quantify morphological and protein-expression changes induced by TGFβ treatment (11).…”
Section: Cell Culture and Tgfβ Treatmentmentioning
confidence: 56%
“…Third, the combined effect of EMT and fibrillar maturation on motility is seen not only at the level of single-cell motility, but also at the level of migration response to pairwise cell-cell interactions. We recently showed that when non-transformed epithelial cells encounter another cell along a fiber-like track, they reverse direction (11,15). Progression through TGFβ-mediated EMT shifts this behavior, enabling cells to slide past each other and continue to move in their original direction.…”
Section: Emt Enhances Motility In An Already Motogoenic Fibrillar Micmentioning
confidence: 99%
See 1 more Smart Citation
“…Migration of non-transformed human mammary epithelial cells (MCF10A) expressing histone 2B-GFP (nuclear marker) and GM130-RFP (Golgi marker) was imaged on micropatterned lines of collagen as detailed in [ 15 ]. MCF10A cells were maintained and passaged using standard growth medium and tissue culture protocols [ 16 , 17 ]. Additionally, to analyze how EMT affects relationships among nucleus and Golgi properties, MCF10A cells were treated with 20 ng/mL TGF β in growth medium for 12 days.…”
Section: Methodsmentioning
confidence: 99%
“…Most unexpectedly, our analysis shows that a PCA model built with data from untreated cells is remarkably similar to that built from data collected with TGF β -treated cells. Despite significant changes in gene expression, morphology and motile phenotype induced by TGF β -mediated EMT in these cells [ 15 , 16 ], treatment with TGF β does not significantly affect the relationships among nucleus size, aspect ratio and orientation with migration direction or among Golgi size and nucleus-Golgi separation distance. These results suggest that migration along spatially-confined fiber-like tracks employs a conserved nucleus-Golgi arrangement that is independent of EMT state.…”
Section: Introductionmentioning
confidence: 99%